Upaya Meningkatkan Aktivitas Dan Hasil Belajar Peserta Didik Dengan Menggunakan Metode Realistic Mathematics Education (RME) di SDN 2 Kotagajah Lampung Tengah Tahun Pelajaran 2019/2020 - Asep Yudianto; Nurul Afifah; Isti Fatonah; Suridin Suridin (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The process of teaching and learning mathematics in elementary schools is generally presented in an abstract form, learning is dominated by lectures, exercises, and question and answer methods so that students become passive and find it difficult to understand the material. This study aims to determine the level of activity and student learning outcomes in mathematics class VA students of SDN 2 Kotagajah. So that mathematics learning activities can be felt meaningful and produce activity and learning outcomes as well as learning objectives to be achieved properly is to apply the approach of realistic mathematics education (RME). Realistic Mathematics Education (RME) is an approach that emphasizes the conceptualization of teaching and has a tendency for students to become active participants in the teaching and learning process. This research is a classroom action research with data analysis in the form of qualitative and quantitative analysis using test data collection tools, observation, and documentation. This study concludes that there is a relationship between student activity and learning outcomes and the use of successful methods to achieve the desired targets. The average percentage of student activity in the first cycle was 67% and remembering as much as 11% and in the second cycle was 78%. The percentage of completeness of learning outcomes reached 52% and 76% in cycle II. So, there was an increase in learning outcomes from cycle I to cycle II, which was 24%.